Analisis Rencana Pelaksanaan Pembelajaran Ilmu Pengetahuan Alam dari Guru Sekolah Dasar - Luthpi Safahi (Jurnal Inovasi Pendidikan Dasar, 2017)
This study aims to describe the ability of elementary school teachers in preparing, formulating and adapting the components of science lesson plan with National Education Standards. This research method was qualitative descriptive method with survey and documentation techniques. The sample was 28 people that was obtained using purposive sampling technique. The research instruments were form of RPP component analysis that consist of 10 components and professional development questionnaires. Most of science RPP format that created by elementary school teacher in Bengkulu was obtained that 85.7% are matched with the CSP format standard and the characteristics of science lesson. The formulation of each component of RPP such as suitability indicators to SK / KD, clarity of KBM detail, method, media, learning resources, suitability of the material, and the goal of the assessment were good because the majority of respondents (60.71%) have drawn up the component of RPP accordance with the standards and characteristics of science lesson. While the development of indicators is aimed to cognitive level and the allocation of time was still lack of management.